Nutritional deficiencies in bariatric surgery patients: a comparison between Roux-en-Y Gastric Bypass and Sleeve Gastrectomy - Ana Sofia de Seabra Vieira (2021)
Background: Obesity is a worldwide epidemic and bariatric surgery is the best recognized treatment option for sustained weight reduction and obesity-related comorbidities. The most used procedures are sleeve gastrectomy (SG) and Roux-en-Y gastric bypass (RYGB). Nutritional deficiencies can have severe consequences and remain one of the most significant side effects of bariatric surgery. Objective: To compare the incidence of nutritional deficiencies in patients undergoing RYGB and SG. Methods: Retrospective analysis of the nutritional status of 505 consecutive patients submitted to either RYGB and SG, between January and December 2019. Data was collected regarding preoperative, 6- and 12-months after surgery levels of vitamin B12, folic acid, vitamin D, calcium, PTH, magnesium, hemoglobin, iron, ferritin and transferrin. Results: The RYGB group presented significantly higher excess weight loss. Regarding the median values of the nutrients, there were multiple significant differences between the two surgical techniques, such as for vitamin B12, hemoglobin and ferritin, all superior in the SG group, throughout the study period. The most marked deficiency was for vitamin D, although with no significant difference between RYGB and SG (62.05% vs 74.24% preoperatively; 29.64% vs 24.03% at 6 months; 22.41% vs 31.48% at 12 months). Vitamin B12 deficiency was significantly higher in the RYGB group (17.46% vs 4.69%, p<0.001 at 6 months and 16.74% vs 0.93%, p<0.001 at 12 months). Conclusion: Both RYGB and SG were associated with several nutritional deficiencies, despite differing in the causing mechanisms. It is crucial to efficiently assess, prevent and manage these deficiencies, according to the surgical procedure.